STAPHYLOCOCCAL SCALDED SKIN SYNDROME MIMICKING TOXIC EPIDERMAL NECROLYSIS IN A HEALTHY ADULT - Tomoko Oishi; Yuka Hanami; Yasunobu Kato; Mikio Otsuka; Toshiyuki Yamamoto (Our Dermatology Online, 2013)
Introduction: Staphylococcal scaled skin syndrome (SSSS) presents generalized form bullous impetigo caused by Staphylococcus aureus (S. aureus) infection, typically seen in infants and children. SSSS may occur also in adults; however, the majority of adult cases are those with immunosuppression. Atypical clinical features of impetigo in adults sometimes make it difficult to diagnose correctly. Case Report: A 74-year-old healthy woman was hospitalized, complaining of extensive desquamative erythema and a number of erosions. She was administered oral antiviral drugs under suspicion of herpes zoster prior to 10 days. Initial diagnosis on the admission was toxic epidermal necrolysis (TEN) due to antiviral tablets; however, steroid pulse therapy resulted in no effect. Bacterial culture yielded coagulase-positive methicillin-resistent S. aureus, producing exfoliative toxin B. A biopsy specimen showed subcorneal splitting of the epidermis. The diffuse erosions gradually improved over 10 days by the treatment with intravenous antibiotics. Conclusions: The differentiation between streptococcal scaled skin syndrome (SSSS) and TEN is sometimes difficult. It is important to remind SSSS when we suspect TEN, even in healthy adults..